2020
DOI: 10.1136/vr.105123
|View full text |Cite
|
Sign up to set email alerts
|

Survival and fertility of bitches undergoing caesarean section

Abstract: BackgroundWith the increasing popularity of planned caesarean section, the need for knowledge regarding this surgery has become increasingly important. The reported death and survival rates for caesarean sections vary widely. Another important aspect is the fertility rate in subsequent oestrous after caesarean section. The aim of this study was to investigate the mortality and survival rate of bitches during caesarean section. Additionally, the fertility of bitches after caesarean sections was determined.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The number of cesarean sections has increased, due to the popularity of this procedure in animals of specific breeds, in addition to cases of dystocia (CONZE et al, 2019). The 17 cases of dystocia in the present study had a surgical approach and accounted for 5.5% of all cases.…”
Section: 8%mentioning
confidence: 70%
“…The number of cesarean sections has increased, due to the popularity of this procedure in animals of specific breeds, in addition to cases of dystocia (CONZE et al, 2019). The 17 cases of dystocia in the present study had a surgical approach and accounted for 5.5% of all cases.…”
Section: 8%mentioning
confidence: 70%
“…This seems to play a subordinate role in dog breeding. In the study by Conze et al ( 17 ) pregnancy rates of 100% were found in 55 bitches within the 2 years following parturition. However, there was a lack of more precise data as to how often the bitches were bred again before getting pregnant.…”
Section: Discussionmentioning
confidence: 94%
“…Of these, nine delivered puppies. This indicates high fertility, but in the study by Conze et al ( 17 ), only a small population of bitches was examined, which limits the strength of their conclusions. These numbers have to be compared to normal pregnancy rates, which are between 78 and 97% ( 19 21 ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations